2016
DOI: 10.4103/0976-9668.175075
|View full text |Cite
|
Sign up to set email alerts
|

Effective factors in controlling diabetes progression among patients in the northwest of Iran

Abstract: Background:Diabetes is the fifth leading cause of death in the world. Hence, we investigated the factors affecting disease control among diabetic patients referred to Imam Reza Hospital (central hospital in the Northwest of Iran).Materials and Methods:One hundred and eight diabetic patients were evaluated. Patient's main medications including insulin, metformin, glibenclamide, and glytazon were registered and the levels of fasting blood sugar (FBS), glucose 2 h postprandial (pp), and hemoglobin A1c (HbA1c) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Almost all the people living in these areas have Azari-Turkish background with different sociocultural values influencing their lifestyle. Diabetes is a major concern in these areas [22, 23] where not only have previous studies shown inadequate diabetes care and high prevalence of complications but relatively poor quality of life among these people has been referred to as well [2427]. …”
Section: Introductionmentioning
confidence: 99%
“…Almost all the people living in these areas have Azari-Turkish background with different sociocultural values influencing their lifestyle. Diabetes is a major concern in these areas [22, 23] where not only have previous studies shown inadequate diabetes care and high prevalence of complications but relatively poor quality of life among these people has been referred to as well [2427]. …”
Section: Introductionmentioning
confidence: 99%